Surgical item left in the abdomen six years after abdominoplasty: case report - Glayse June Sasaki Favarin; Eduardo Favarin; Amanda Nunes Borges; Airton Moreira Pinto Junior; Viviane Alessio Baggio; Nicoly de Souza Jacques (Revista Brasileira de Cirurgia Plástica)
The retained surgical item in patients after closure of the wound is a situation that although rare is preventable and requires specific care such as institutional protocols for prevention. We report a case of removal of an already encapsulated pads by fibrin tissue (textiloma) from a patient six years after an abdominoplasty, which formed a palpable mass in her abdomen. The retained surgical items lead to variable symptoms such as palpable masses, compressions, non-absorptive loss and, sometimes, severe complications. The diversity of manifestations combined with their few frequency, most of the times, lead to underdiagnosis. Treatment should be individualized for each case, although in case of symptoms removal is indicated in most cases. Surgical removal is associated with complications as longer as objects remain in patient's body.